Trends in basal cell carcinoma incidence rates: a 16-year retrospective study of a population in central Poland - Ciążyńska, Magdalena; Narbutt, Joanna; Woźniacka, Anna; Lesiak, Aleksandra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Introduction : Basal cell carcinoma (BCC) is the most commonly occurring cancer worldwide, and the overall incidence is still rising. Unfortunately, the cancer registry in Poland does not record BCC individually. Thus, the incidence of BCC in a defined population is unknown. Aim : Analysis of incidence rates of primary BCC in central Poland during 16 years considering sex, site distribution and age to determine trends. Material and methods : We retrospectively included all cases of BCC which were diagnosed and treated in the Department of Dermatology and Venereology, Medical University of Lodz, during the 16-year period from 1999 to 2015. Results : We recorded 945 BCCs occurring in 890 patients (504 females – 57%, 386 males – 43%). Patient’s age was between 21 and 94. A distinct increase in BCC was observed after 1999, while after 2010 during the next 2-year period a slight decrease was noted. A statistically significant correlation was observed between histopathological types of BCC and the location of the lesions. The superficial type predominates on photoprotected areas, especially on the trunk, while the nodular type occurs mainly in facial areas. No statistically significant correlation was observed between histopathological types of BCC and sex. We found a significant increase in incidence for superficial BCC among middle-age patients, while the nodular type was observed more frequently among elderly subjects. Conclusions : Basal cell carcinoma is quite common in Poland and predominantly develops in the facial area. In middle-age patients the most common is superficial BCC, while in elderly people the nodular type is most common. Based on our results we assume that there is a strong need to educate general physicians to enable them to diagnose BCC in the early stages.